Mathematical modeling analyses for obtaining an optimal railway track maintenance schedule - Oyama, Tatsuo; Miwa, Masashi (Japan journal of industrial and applied mathematics, 2006)
Railway track irregularities need to be kept at a satisfactory level by taking appropriate maintenance activities. This paper aims at obtaining an optimal maintenance schedule for improving the railway track irregularities using all-integer linear programming (AILP) optimization model analyses. Firstly, we try to predict a change of surface irregularities by investigating the transition process through degradation and restoration model analyses. Then we develop an AILP model for obtaining an optimal schedule of multiple tie tamper (MTT) operation. The model takes both maintenance costs and the level of surface irregularities that reflects riding quality and safety into account, then finally gives an optimal tamping schedule of MTT for the whole year. Then we apply the results of this model to solve the optimal MTT's maintenance scheduling problem for the actual railway network system and show that it is effective and useful enough by comparing our model results with actual existing data.[PUBLICATION ABSTRACT]